(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The objective of this study was to determine the prevalence of urinary tract infection (UTI) and antibiotic sensitivity pattern among the suspected UTI cases visiting at Ganeshman Singh Memorial Hospital Lalitpur, Nepal. Methods: A total of 300 mid-stream urine, catheter and suprapubic aspirate from UTI suspected patients were included and processed for routine microscopy and culture and then identified by standard microbiological methods. Antibiotic susceptibility test was performed by Kirby- Bauer disc diffusion method. Results: Out of 300 samples, 55(84.6%) mid-stream urine and 10(15.4%) catheter sample had significant bacterial growth. E. coli (32,49.2%) was the most common isolate followed by Staphylococcus aureus (10,15.3%), Enterobacter spp. (8,12.3%), Klebsiella spp. (7,10.7%), Pseudomonas aeruginosa (3,4.6%), Proteus spp. (3,4.6%), Acinetobacter spp. (1,1.5%) and Enterococcus spp. (1,1.5%). Most of the Gram-negative bacterial isolates were sensitive to Ceftriaxone (88.8%) followed by Gentamicin (72.2%), and Nitrofurantoin (64.8%) and resistant to Amoxicilin (68.5%) followed by Nalidixic Acid (53.7%). Gram positive isolates were sensitive to Amikacin (72.7%) followed by Imipenem (63.6%) and Gentamicin (63.6%) whereas resistant to Amoxycilin (72.7%) and Ciprofloxacin (63.63%). Conclusion: The main cause of the UTIs was found as Gram negative bacteria. Prescription of antibiotics based on susceptibility tests would help in reduction of antibiotic resistance.